The chromosomal passenger complex: regulation of chromosome segregation in kinetoplastids - Ballmer, D (2024)
An intricate network of kinases and phosphatases safeguards the fidelity and timeliness of chromosome segregation in eukaryotes. As the catalytic subunit of the chromosomal passenger complex (CPC), the Aurora B kinase plays a pivotal role within this network by destabilizing improper kinetochore-microtubule attachments and relaying the attachment status to the spindle assembly checkpoint. Intriguingly, Aurora B is conserved even in kinetoplastids, an evolutionarily divergent group of eukaryotes, who lack a canonical spindle checkpoint, and whose kinetochores are composed of a unique set of structural and regulatory proteins. It remains unknown how chromosome segregation and mitotic exit are controlled in kinetoplastids, and whether the CPC contributes to these processes as in other eukaryotes. A deeper understanding of the mitotic regulatory circuitry in kinetoplastids is bound to provide evolutionary insights into fundamental principles of cell division in eukaryotes and can lead to the discovery of druggable targets to combat infectious diseases caused by kinetoplastid parasites (e.g. sleeping sickness, Chagas disease, and leishmaniasis).